2002
DOI: 10.1046/j.1540-8167.2002.00645.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Significance of Intermittent Pulmonary Vein Tachycardia in Patients with Atrial Fibrillation

Abstract: Intermittent bursts of tachycardia are observed within multiple PVs during persistent AF in a majority of patients. After PV isolation, PV tachycardias almost always resolve, and AF is less likely to be inducible or persistent. These observations suggest a dynamic interplay between the atria and PVs, with intermittent bursts of PV tachycardia being dependent on left atrial input and with the probability of persistent AF diminishing when PV tachycardias are eliminated by PV isolation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
181
3
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 180 publications
(197 citation statements)
references
References 7 publications
12
181
3
1
Order By: Relevance
“…(2) Can these mechanisms be accurately identified and targeted? and (3) Do targeted ablation strategies improve patient outcomes?…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(2) Can these mechanisms be accurately identified and targeted? and (3) Do targeted ablation strategies improve patient outcomes?…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Antral isolation of PVs and elimination of focal triggers and drivers from other thoracic veins often result in termination and noninducibility of PAF in response to various pharmacological and pacing protocols. Patients with PAF whose AF terminated during ablation and were rendered noninducible, also were more likely to remain in sinus rhythm during long-term clinical follow-up.…”
Section: Mechanistic Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11][12][13] Pulmonary vein tachycardia usually occurs in short bursts, and can be recognized during an episode of AF by the presence of a shorter atrial cycle length within a pulmonary vein than in the adjacent left atrium (Fig 1). 11 Several lines of evidence indicate that these bursts of rapid electrical activity arise within the pulmonary veins, as opposed to representing fractionation of the wave fronts that enter the pulmonary veins from the left atrium. 14 Bursts of pulmonary vein tachycardia can be recorded during episodes of paroxysmal AF in approximately 90% of the left superior, left inferior, and right superior pulmonary veins, and less commonly in the right inferior pulmonary vein.…”
Section: Role Of Pulmonary Veins In Atrial Fibrillationmentioning
confidence: 99%
“…14 Bursts of pulmonary vein tachycardia can be recorded during episodes of paroxysmal AF in approximately 90% of the left superior, left inferior, and right superior pulmonary veins, and less commonly in the right inferior pulmonary vein. 11,13 Studies in which attempts are made to induce AF by rapid atrial pacing before and after pulmonary vein isolation have indicated that bursts of pulmonary vein tachycarCirculation Journal Vol.67, July 2003 dia often may play a role in perpetuating an episode of AF, regardless of whether or not the trigger for the episode arose in a pulmonary vein. 11,13 Therefore, pulmonary vein isolation not only may eliminate the triggers for AF, but also may eliminate one of the factors responsible for the maintenance of AF.…”
Section: Role Of Pulmonary Veins In Atrial Fibrillationmentioning
confidence: 99%